Vertical and Horizontal M-Charts and Microperimetry for Assessment of the Visual Function in Patients after Vitrectomy with ILM Peeling due to Stage 4 Macular Hole. (6th May 2019) - Wrzesińska, Dominika; Nowomiejska, Katarzyna; Nowakowska, Dominika; Brzozowska, Agnieszka; Avitabile, Teresio; Reibaldi, Michele; Rejdak, Robert; Toro, Mario
Abstract : Purpose . To examine the relationship between the morphological and functional results in eyes after pars plana vitrectomy (PPV) with internal limiting membrane (ILM) peeling due to stage 4 full-thickness macular hole (FTMH). Methods . The study included 22 eyes that underwent successful PPV due to FTMH. Both vertical metamorphopsia (VM) and horizontal metamorphopsia (HM) were determined using type 2 M-charts, as well as best-corrected visual acuity (BCVA), microperimetry, and optical coherence tomography (OCT) were performed before PPV and 1 and 6 months postoperatively. Results . A significant improvement of BCVA and metamorphopsia scores measured by M-charts in particular periods before surgery, 1 and 6 months after PPV, was observed. The VM scores were consistently higher than the HM scores at all assessment times. There was a correlation found between VM and BCVA and microperimetry parameters before surgery. The macular sensitivity (MS) as well as macular integrity index increased from 1 month to 6 months after PPV and were correlated with postoperative visual acuity (VA). There was a correlation found between the hole diameter and MS and P2 parameter 6 months after PPV. There was a correlation found between mean duration of symptoms of FTMH and VA and VM score. Conclusions . VM scores seem to correlate better than HM scores with preoperative BCVA, microperimetry parameters, and duration of symptoms of the FTMH. VM scores are higher after PPV than HM scores in patients with stage 4 of the FTMH. This trial is registered withNCT03701542 .